THE IMPACT OF INTANGIBLE ASSETS ON FIRM VALUE AND PERFORMANCE: EVIDENCE FROM ASIA-PACIFIC INFORMATION TECHNOLOGY COMPANIES - JO, Abraham Abner Jo; Nugroho, Vina Christina (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study explores how intangible assets (IA) influence firm value and financial performance among publicly listed Information Technology (IT) companies in the Asia-Pacific region over the period 2013 to 2023. It focuses on three key components of IA which is identified intangible assets (IIA), goodwill (GW), and research and development (R&D) and uses panel data regression, specifically the Random Effects Model, to assess their impact on firm value (measured by Tobin’s Q) and firm performance (measured by ROA and ROE). The analysis covers 306 companies, categorized into two groups: intangible-intensive (IIP) and non-intangible-intensive (non-IIP) firms, based on the proportion of intangible assets to total assets. The results shows that R&D spending is associated with lower Tobin’s Q, it positively contributes to ROE, suggesting that although R&D may dampen short-term market valuation, it supports long-term profitability. On the other hand, identifiable intangibles are linked to lower ROE and show varied effects on Tobin’s Q depending on a firm’s IA intensity. Interestingly, firms with higher IA intensity do not consistently outperform their less intangible-intensive peers, challenging the idea that more IA always translates to higher value.